Optimization of nutrition of the russians — a way to longevity and quality of life - V. A. Tutelyan; B. P. Sukhanov; M. G. Kerimova; E. V. Elizarova (Сеченовский вестник)
The review article presents data on the nutritional status and health of the Russians in the dynamics of the last decade, sets out the most relevant provisions of policy documents (2010), aimed at optimizing the nutrition and reducing the risk of nutrition-related diseases, shows the tasks and ways of implementation of the state policy in the field of healthy nutrition of the Russian population at the federal and regional levels.